Simultaneous strengthening and toughening of composite T-joints by microstructuring the adhesive bondline. (November 2022) - Wagih, A.; Hashem, M.; Lubineau, G.
Abstract: A bioinspired adhesive T-joint that mimics the bondline in Mytilus californianus was developed to address the challenge of simultaneously increasing the strength and toughness of T-joints, microstructured by embedding artificial voids in the bondline between the skin and the stiffener. For 1 mm adhesive thickness, the strength and toughness of the bioinspired adhesive T-joint reached 3.27 and 18.9 times those of the conventional T-joint during the pull-off test, respectively, which can be attributed to the change in degradation mechanism when the toughness of the adhesive bondline exceeding that of the substrate causes energy dissipation in the composite fracture. Moreover, the progressive damage mode of the bioinspired adhesive T-joint protects it against complete failure.